2021
DOI: 10.1080/10799893.2021.1967392
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-199a downregulation alleviates hyperuricemic nephropathy via the PPARγ/β-catenin axis

Abstract: Hyperuricemia always develops into hyperuricemic nephropathy (HN). The role of microRNA (miR) in HN is less studied. We aimed to discuss the role of miR-199a in HN. The expression of miR-199a and PPARc in renal tissues of HN rats was detected. The targeting relation between miR-199a and PPARc was verified. The contents of SCr, UA, BUN, and mALB, renal injury-relevant biomarkers were detected, and the pathological changes of renal tissue and renal interstitial fibrosis were observed by histological staining. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The miR-199a-5p and -3p can be generated from miR-199a-1 and -2 precursors and both can influence the TGF-β pathway. For instance, miR-199a-5p was reported to inhibit endoplasmic reticulum stress in renal ischemia-reperfusion (I/R) injury [45] and to downregulate PPARγ, exacerbating renal interstitial fibrosis in rats with hyperuricemia [28]. Elevated miR-199a-5p has been reported in mouse and human CKD as well, underscoring its potential importance [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The miR-199a-5p and -3p can be generated from miR-199a-1 and -2 precursors and both can influence the TGF-β pathway. For instance, miR-199a-5p was reported to inhibit endoplasmic reticulum stress in renal ischemia-reperfusion (I/R) injury [45] and to downregulate PPARγ, exacerbating renal interstitial fibrosis in rats with hyperuricemia [28]. Elevated miR-199a-5p has been reported in mouse and human CKD as well, underscoring its potential importance [30].…”
Section: Discussionmentioning
confidence: 99%
“…Both miR-199a-3p and miR199a-5p are potential regulatory factors of TGF-β-mediated pathological renal processes [28][29][30]. TGF-β administration markedly increased the expressions of both miR-199a-3p and miR-199a-5p in primary mouse tubular epithelial cells, which were inhibited by pioglitazone (Figure 5C,E).…”
Section: Pioglitazone Restores the Expression Of Tgf-β-induced "Fibro...mentioning
confidence: 93%
See 1 more Smart Citation
“…For example, the increasing evidence has suggested that the development of hyperuricemia and gout is regulated at the post transcriptional level with strong involvement of miRNAs ( 24 ). Furthermore, studies have revealed abnormal expressions of miRNAs involved in hyperuricemia and the association between serum UA concentration and altered expressions of miRNAs ( 25 ). In particular, miRNAs could regulate the expression of urate transporter genes, e.g., miR-34a regulates the mRNA of the solute carrier family 22 member 12 ( SLC22A12 ) gene to ultimately repress the uric acid transporter 1 (URAT1) expression in the animal model of hyperuricemia ( 26 ).…”
Section: Introductionmentioning
confidence: 99%